Constructing Boolean Matrices with Restriction Enzymes as Row/Column Indicators in DNA Computing - Nordiana, Rajaee; Kismet, Hong Ping; Asrani, Lit; Dayang Nur Salmi Dharmiza, Awang Salleh; Ng, Liang Yew (2014)
The design and strategy to encode problems into DNA sequences for computation gives different advantages and limitations during extraction of their results. In this paper, we study the utilization of restriction enzymes as row/column indicators in the modeling and computing of Boolean matrices in DNA computing. We discuss the highlights, drawbacks and applicability of the restriction enzymes during the encoding of the problems in DNA computing.